The Peruvian government's use of the State of Emergency during the pandemic and its compliance with International Human Rights Law - Huamán, Brenda (2022)
This paper studies the states of emergency declared in Peru during the COVID-19 pandemic, a time frime that began with the arrival of this virus to Peru during the government of Martin Vizcarra and continues up to the present. In this way, it is explained that the «normalisation» of the use of states of emergency has remained a recurrent trend in Peruvian politics during the period analysed, and that this practice does not usually meet the international standards required for its establishment, such as the principles of legality, proclamation, notification, exceptionality, necessity and proportionality, temporality, non-discrimination, and compatibility with international law. After analysing each of these principles, the text reveals that during the period studied this figure has been used consistently to prevent the spread of the virus and its variants, to re-establish social coexistence, but also to address situations of social conflict, increased public insecurity, organised crime and to combat terrorist remnants. It is also identified that, in general, this government practice has directly and indirectly limitedthe exercise of different human rights of the inhabitants without any reasonable justification.